2002
DOI: 10.1046/j.1440-1819.2002.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements during the Rorschach test in schizophrenia

Abstract: In order to understand relationships between scanning behaviors, characteristics of visual stimuli and the clinical symptoms in schizophrenia, eye movements of 37 schizophrenic patients and 36 controls were recorded using an eye-mark recorder during a free-response period in a Rorschach test. Four cards (I, II, V and VIII) were used. Data were analyzed during 15 s from the presentation of each card. For all cards, the number of eye fixations and the number of eye fixation areas were fewer, and total scanning l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 12 publications
2
27
0
6
Order By: Relevance
“…Changes in visual scan pattern was found in other studies indicating that eye movement properties are altered in schizophrenia patients 6,[11][12][13]23,24 and in their first-degree relatives 4 . Eye movement studies show that even in simple tasks, such as saccades directed to a target, the generation of eye movements is mediated by bottom-up sensorial processes and top-down complex cognitive processes.…”
Section: Analysis Of Eye Movementssupporting
confidence: 59%
See 4 more Smart Citations
“…Changes in visual scan pattern was found in other studies indicating that eye movement properties are altered in schizophrenia patients 6,[11][12][13]23,24 and in their first-degree relatives 4 . Eye movement studies show that even in simple tasks, such as saccades directed to a target, the generation of eye movements is mediated by bottom-up sensorial processes and top-down complex cognitive processes.…”
Section: Analysis Of Eye Movementssupporting
confidence: 59%
“…To what extent this is due to medication remains unclear. Studies correlating eye movement properties, symptomatology and medication dose have shown discordant results 6,[11][12][13]23,28 . Controlled studies comparing the effects of risperidone and olanzapine have found a decrease in the mean length of the saccadic movements in schizophrenia patients compared to controls but no difference was found among patients due to the medication type 30 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations